A new player in the orchestra of cell growth: SREBP activity is regulated by mTORC1 and contributes to the regulation of cell and organ size. (20th January 2009) - Porstmann, Thomas; Santos, Claudio R.; Lewis, Caroline; Griffiths, Beatrice; Schulze, Almut
Abstract : Cell growth requires co-ordinated regulation of processes that provide metabolites for the synthesis of macromolecules such as proteins and membrane lipids. In recent years, a lot of emphasis has been placed on the activation of protein synthesis by mTORC1 (mammalian target of rapamycin complex 1). The contribution of anabolic pathways other than protein synthesis has only been considered recently. In the present paper, we discuss recent findings regarding the contribution of transcriptional regulation of lipogenesis genes by the SREBP (sterol-regulatory-element-binding protein) transcription factor, a central regulator of expression of lipogenic genes, to the control of cell size in vitro and cell and organ size in vivo .